Meningkatkan Work-Life Balance pada BUMN Sesuai dengan Core Value Akhlak - Pradika Sulaeman (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the relationship between work-life balance and AKHLAK core values ​​in the context of employee performance in Indonesian State-Owned Enterprises (BUMN). Work-life balance has been proven to be an important factor in improving employee performance and well-being, but there has been little research exploring how AKHLAK core values—including Amanah, Kompeten, Harmonis, Loyal, Adaptif, and Kolaboratif—can support the achievement of work-life balance in BUMN. This study uses a qualitative approach with document analysis, observation, and in-depth interviews in several BUMN in Indonesia. The results of the study indicate a significant relationship between work-life balance and AKHLAK core values. Work-life balance sub-parameters such as work time effectiveness, involvement in work, work schedule flexibility, and manager support are positively correlated with AKHLAK values, such as Kompeten, Kolaboratif, and Adaptif. This study also found that the implementation of AKHLAK core values ​​can create a healthier and more harmonious work environment, which ultimately improves employee retention and performance. Therefore, the implementation of AKHLAK values ​​needs to be strengthened by policy makers in BUMN to achieve optimal work balance, which contributes to improving overall organizational performance. This study is expected to be a strategic recommendation for BUMN in implementing work-life balance policies based on AKHLAK values.